Android-Based Internship Attendance and Logbook Application Using Geofence Technology - Hidayat, Almisri; Sanatang, Sanatang; Fajar B, Muhammad (PT. Lontara Digitech Indonesia, 2025)
Internship activities among students are generally still carried out using manual attendance and logbook recording systems, such as signature sheets or written notes. These conventional methods often lead to inefficiencies, delays in data processing, and potential manipulation of attendance records. Therefore, a digital system is needed to monitor student attendance automatically and accurately based on their actual location. This study aims to develop an Android-based internship attendance and logbook application utilizing geofence technology. The application is designed as a solution to the limitations of manual systems by providing location-based attendance features, daily logbook recording, and an integrated dashboard accessible to students, supervisors, and administrators. The development process adopts the Waterfall model, which includes the stages of requirement analysis, system design, implementation, testing, and maintenance. The system only allows attendance when the user is within the predefined internship location radius, thereby ensuring the validity and accuracy of attendance data. Testing was conducted based on the ISO/IEC 25010 quality standard, covering aspects of Functional Suitability, Usability, Performance Efficiency, Compatibility, and Security. The results show that the application achieved a very good level of feasibility, with a usability score of 89%, an average response time of 2.21 seconds, good compatibility across various Android devices, and a Security Grade A rating. Based on these results, the developed application is declared feasible for use and can serve as an effective solution to support student internship activities in a digital, accurate, and efficient manner.